Component Reliability and Fleet Utilization for Spare Parts Management at Sidotopo Locomotive Depot - Abdul Rochim; Niniet Indah Arvitrida; Suparno (Universitas Panca Marga, 2026)
Locomotive reliability and spare parts availability are essential for maintaining railway operational performance and service continuity. However, previous studies have generally focused on component reliability or inventory management separately, with limited attention to integrating component reliability, fleet utilization, and spare parts demand characteristics into a unified framework for spare parts management. This study aims to address this gap by developing a reliability-based approach for identifying critical spare parts at Sidotopo Locomotive Depot, Operational Region 8 Surabaya, PT Kereta Api Indonesia (Persero). Historical maintenance and operational data were analyzed using Pareto analysis, material reconciliation, expert judgment, reliability analysis, fleet utilization assessment, and demand pattern classification. The analysis identified four critical components: AEP5, Victaulic 3.5